Keberlanjutan Dan Perubahan Tari Angguk Grobogan di Sanggar Seni Kanastren - Anggun Lydia Maharani Anggun; Joko Wiyoso (KOLONI, 2026)
The Angguk Grobogan Dance is a traditional art form that has grown and developed within the community of Grobogan Regency, Central Java. As an intangible cultural heritage, the Angguk Dance possesses historical, religious, social, and aesthetic values ​​that reflect the identity of its supporters. However, globalization, modernization, technological developments, and changing public tastes pose challenges that impact the sustainability of this traditional art form. This study aims to further explore the desires and changes in the Angguk Grobogan Dance within the context of productions conducted by the Kanastren Art Studio. This study employed a qualitative approach with a descriptive approach. The research location was the Kanastren Art Studio, Grobogan Regency, Central Java. Data collection techniques included observation, in-depth interviews, and documentation. The data obtained were explained using Koentjaraningrat's theory of cultural change to understand the relationship between tradition preservation and the process of cultural adaptation that occurs in the Angguk Grobogan Dance. The results of the study indicate that the desire for the Angguk Grobogan Dance at the Kanastren Art Studio is realized through routine practice, continuous performances, the regeneration process of dancers from various age groups, and the inheritance of cultural values ​​​​contained in the dance. In addition, the study found various forms of change that occurred in the Angguk Grobogan Dance, including changes in musical accompaniment, development of dance movements, adjustments to costumes, and changes in aspects of the dancers. Based on the results of the study, it can be concluded that desire and change are two complementary processes in the preservation of the Angguk Grobogan Dance. Cultural preservation does not have to be done by maintaining old forms rigidly, but can be realized through innovation that remains grounded in traditional values.